Study of hydrochemical and geochemical characteristics and solute fluxes in Upper Ganga Basin, India. Issue 8 (1st December 2022) - Sharma, M.K.; Kumar, Pradeep; Prajapati, Parul; Bhanot, Kunarika; Wadhwa, Udita; Tomar, Garima; Goyal, Rakesh; Prasad, Beena; Sharma, Babita
Highlights: COD and TSS exceeded the prescribed criteria limit for drinking purpose. HCO3 and SO4 were observed as the dominant anions. Peculiar behaviour of SO4 was observed along the River Bhagirathi. Significant correlation observed between flux and river discharge in Bhagirathi. Abstract: Himalayan rivers are considered the most sensitive of all the ecosystems to the impact of climate change. In the present investigation, hydrochemical processes controlling the meltwater chemistry of the rivers Bhagirathi, Alaknanda and Ganga in the Upper Ganga Basin, India have been studied simultaneously creating a large database for the first time. For this purpose, an extensive water quality assessment in Upper Ganga Basin has been carried out by collecting water samples from all three rivers on monthly basis from September 2016 to May 2018 and analysing these samples for hydro-chemical parameters. Hydro-chemical characteristics revealed that sulphide oxidation and carbonation- the two proton producing reactions govern the chemical weathering processes pertaining in the rivers. One of the most peculiar findings of the study is the dominance of carbonate dissolution in the whole stretch of River Alaknanda, while the dominance of sulphide oxidation in River Bhagirathi upto Dabrani revealing the continuum of Gangotri glacial processes followed by carbonate dissolution upto Haridwar. The principal component analysis further supports this weathering process in the basin.